PENGARUH WAKTU FERMENTASI BAHAN ORGANIK (KOTORAN AYAM, AMPAS TAHU DAN ROTI AFKIR) SEBAGAI PUPUK UNTUK PERTUMBUHAN DAN KANDUNGAN PROTEIN Daphnia sp. - Endra Catur Pamungkas; Johannes Hutabarat; Vivi Endar Herawati (Pena Akuatika Jurnal Ilmiah Perikanan Dan Kelautan, 2017)
This research aims to know the influence of the time of fermentation of organic matter (chicken mature, tofu waste and bread waste) that’s different to protein content of fertilizer of Daphnia sp.’s culture media and determine the best treatment to produce the protein content of fertilizer of Daphnia sp.’s culture media, growth, biomass and protein content on Daphnia sp.. This research used laboratory animals such as Daphnia sp. and a container of concrete tanks as many as 12. The methods of this research used experimental methods with Complete Random Design with 4 treatments and 3 repetition with the density of the Daphnia sp. was 100 ind./l with a dose of fertilizers is 25 % chicken manure, 25 % tofu waste and 50 % bread the total amount of the combination was 2 g/l. Treatments of this research were Treatment A (0 days fermentation without EM4), B (7 days fermentation), C (14 days fermentation), D (21 days fermentation). The results showed that the treatment of C was the highest protein content of fertilizer is 20.10%, population density valued 1036.73 ind/ml, biomass in treatment C resulted averaged in 130.40 gram, the content of protein is 67.49%, specific growth rate with a value of 0.671/day. The conclusion of this research that was found from the addition of the combination organic material (chicken manure, tofu waste and bread waste) with different fermentation time gave significant difference (P<0,01) on nutritional fertilizers, growth, biomass, and nutrient contents of Daphnia sp.Keywords : Daphnia sp., time of fermentation, protein